Hubungan Antara Persepsi Terhadap Kesejahteraan Karyawan Dengan Kepuasan Kerja Pada Karyawan PT. Delta Merlin Sandang Tekstil I Sragen - Wandansari, Istiqomah; Drs. Mohammad Amir, M. Si, Psi, Drs. Mohammad Amir, M. Si, Psi (2017)
Job satisfaction means that positive attitudes and feelings, one has to work as a result of an assessment of the work. One of the factors that affect job satisfaction is the perception on the welfare of employees. This study aims to determine the relationship between perceptions of employee well-being and job satisfaction, the level of perceptions on welfare of employees, the level of job satisfaction and effective contribution from the perception of the welfare of employees on job satisfaction. Researchers used quantitative methods to achieve the objectives of this research. Subjects in this study were employees of PT Delta Merlin Sandang Tekstils I Sragen active in the work amounted to 50 people. The results of data analysis showed a correlation coefficient (r) is 0.545 with significance (p) = 0.000 (p <0.01). This shows there is a significant positive relationship between perceptions of employee welfare and job satisfaction. Based on the results of analysis of job satisfaction variables have the empirical mean (RE) amounted to 108.78 and the hypothetical mean (RH) of 90 which means job satisfaction research subject is high. Variable perceptions of well-being employees have the empirical mean (RE) of 92.46 and the hypothetical mean (RH) of 85 which means that the perception of the employee welfare of research subjects classified as moderate. Effective contribution from the perception of the welfare of employees amounted to 29.70% on employee job satisfaction